The Performance of Sustainable Development Goals, COVID-19, and Costa Rica Bicentennial (Repertorio Científico, 2020)
Costa Rica was the first country in the world that commit the Sustainable Development Goals (SDG). Five years after this engagement, two voluntary reports and actual effect of global outbreak, this study aims to measure the performance of the SDGs, the effects of COVID-19 and the challenges facing the bicentenary of Costa Rica. A PESTAL environment analysis has been applied, as well an achievement’s matrix of objectives. Regarding the results, the country keep on progress in SDGs 2, 3, 7, 12, 13, and 15;  in contrasts showed delays in goals 1, 6, 8, 11, 14 and 16. While is true that the performance of the SDGs can be affected by the pandemic; it is also correct that we identified historical issues broaden some environmental obligations. In addition to financial policies and economic reactivation steps, it should be promoted projects for national land planning, electromobility, reduction of use of fossil fuel, as well nature-based solutions as route map for governance and of SDG performance.
Keywords: Sustainable Development Goals, PESTEL, COVID-19, Costa Rica Bicentenary